SOCIAL NETWORKS CREATED BY JESUS DURING HIS MINISTRY: A SOCIOLINGUISTIC ANALYSIS OF THE GOSPELS OF MATTHEW AND JOHN (REMUNOM, 2026)
This paper analyzes the social networks created by Jesus during His ministry, based on the Gospels of Matthew and John, and explores how interpersonal interactions and network structures shape social and linguistic behavior. The general objective of this study is to investigate the types of networks formed by Jesus, considering density, multiplexity, and the role these networks played in disseminating His message. The specific objectives include identifying the social groups mentioned in the Gospels, characterizing the networks, and relating them to the spread of Christianity. As a theoretical framework, we draw on authors such as Bortoni-Ricardo (2011, 1985), Labov (1972), Milroy (1980), and Gumperz (1976), who discuss the relationship between social networks and linguistic variation. We adopted a qualitative and descriptive methodology, carrying out documentary analysis and using selected Gospel passages to interpret how social networks were structured and expanded. Our findings show that Jesus built dense and diversified networks, transforming professional and social ties into spiritual connections, as seen in the calling of the disciples (Matthew 4:18-22) and in the interaction with the Samaritan woman (John 4:7-26). In addition, we observe that the “Great Commission” (Matthew 28:19-20) reflects the global expansion of Jesus’ networks.